HOW DOES WORD OF MOUTH AFFECT PURCHASE DECISION?:THE MEDIATING ROLE OF BRAND AWARENESS (Studi Kasus Pada Konsumen Kopi Kulo di Kota Semarang) - Muja, Maria Rosalina; Yuswono, Irawan (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study is to investigate how Word of Mouth (WOM) affects consumers' purchasing decisions for Kulo Coffee in Semarang City, using Brand Awareness as a mediating variable. This study was motivated by the high business competition in the coffee industry, where effective marketing strategies are needed to increase purchasing decisions. The research model developed examines the relationship between WOM, social media marketing, and Brand Awareness on consumer purchasing decisions. Data were collected through questionnaires distributed to 200 respondents. Data analysis was carried out using the Structural Equation Modeling (SEM) method. The results showed that WOM has a significant influence on purchasing decisions, both directly and through Brand Awareness as a mediating variable. In addition, Social Media Marketing was also found to have a significant effect on Brand Awareness and purchasing decisions. This study provides theoretical and practical implications for entrepreneurs in the coffee industry to focus more on increasing Brand Awareness through Word of Mouth and social media marketing to influence consumer purchasing decisions.